COMPETITIVENESS AND INNOVATION SYNTHESIS IN THE INTEGRATED GLOBAL ECONOMY - Jatuliavičienė, Gražina; Kučinskienė, Marija (Ekonomika, 2010)
The article aims to show that the main and most important prerequisite for successful business development in the integrated global market becomes improvement of the competitiveness of countries and business firms finding new ways for economic growth and prosperity. Theoretical and empirical researches highlight the importance of competitiveness in a national framework for business growth and development in the current era of globalization. The article examines how the challenges of competitiveness and innovation interrelate and how their synthesis links with economic growth. Therefore, gaining competitiveness through innovativeness, the capability to be innovative is one of the most important prerequisites for creating successful businesses, sophisticated products and production processes and raising the standards of living.